Does a supplementary preoperative breast MRI in patients with invasive lobular breast cancer change primary and secondary surgical interventions? - Heil, Jörg; Bühler, Anne Laura; Golatta, Michael; Rom, Joachim; Harcos, Aba; Schipp, Anne-Isabell; Rauch, Geraldine; Junkermann, Hans; Sohn, Christof (Annals of surgical oncology, 2011)
We evaluated whether a supplementary preoperative breast MRI in patients with invasive lobular breast cancer (ILC) has changed number and methods of primary and number of secondary surgical interventions.
Gesehen am 28.09.2022